DESAIN PEMBELAJARAN BAHASA INGGRIS MELALUI GOOGLE CLASSROOM - Mastoni, Mastoni; Rahmawati, Rahmawati (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2019)
The rapid development of technology and the internet in recent years has affected the world of education, especially learning methods. You may still remember the feeling of sitting in a classroom with other friends, while a teacher explained the lesson on the board. This method is still applied, but the technological sophistication influences the change in teaching patterns.One such development emerged through Google Classroom which was officially released in August 2014. As the name implies, Google Classroom tries to "move" classrooms to the online domain. So you can still meet the students, it's just now doing it through the screen of each gadget. Practical, right? This study showed that this application can help and facilitate the lecturers and students in carrying out the learning process in depth. This was because both students and lecturers can collect the assignments, distribute the assignments, and assess the assignments at home or anywhere without being bound by time limits or hours of study.